In-Vitro characterization of gastroretentive microballoons prepared by the emulsion solvent diffusion method - Akash Yadav; Dinesh Kumar Jain (Wolters Kluwer Medknow Publications, 2010)
Microballoons floatable on JPXIII No.1 solution were developed as a dosage form capable of floating in the stomach. Microballoons were prepared by the emulsion solvent diffusion method using enteric acrylic and other polymers with drug in a mixture of dichloromethane and ethanol. It was found that preparation temperature determined the formation of cavity inside the microsphere and the surface smoothness, determining the floatability and the drug release rate of the microballoons. The correlation between the buoyancy of microballoons and their physical properties, e.g. apparent density and roundness of microballoons were elucidated. The drug loading efficiency of microballoons was also determined. The optimum loading amount of metformin in the microballoons was found to impart ideal floatable properties to the microballoons. By fitting the data into zero order, first order and Highuchi model it was concluded that the release followed zero order release.